2010
DOI: 10.1680/stbu.2010.163.5.299
|View full text |Cite
|
Sign up to set email alerts
|

Reinforced jet-grouted piles. Part 1: analysis and design

Abstract: This two-part set of papers reports some recent experiences in the design of jet-grouted piles (under predominantly lateral load) when their intended use is primarily structural, as is certainly the case when reinforcing steel is present. Although unusual, a number of such design solutions have been documented – several of them recent and applied to major structures. In the absence of specialist rules for the design of jet-grouted piles with steel reinforcement, codes of practice for reinforced concrete (RC) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
0
6
1
1
Order By: Relevance
“…The absolute values for the average compressive strength measured for all different soilcrete samples (between 17 and 57 MPa in range) were significantly higher than those reported in similar studies found in the literature (between 1 and 15 MPa) not only in soil-based structural members but also in grouting applications and repair mortars [6,7,18,21,22,[33][34][35]. Even though a list of crucial design parameters such as the soil's origin and physicochemical properties, the selected binder synthesis, the chosen W/B ratio, the potential use of special additives (i.e.…”
Section: Compressive Strength Testscontrasting
confidence: 57%
See 4 more Smart Citations
“…The absolute values for the average compressive strength measured for all different soilcrete samples (between 17 and 57 MPa in range) were significantly higher than those reported in similar studies found in the literature (between 1 and 15 MPa) not only in soil-based structural members but also in grouting applications and repair mortars [6,7,18,21,22,[33][34][35]. Even though a list of crucial design parameters such as the soil's origin and physicochemical properties, the selected binder synthesis, the chosen W/B ratio, the potential use of special additives (i.e.…”
Section: Compressive Strength Testscontrasting
confidence: 57%
“…A natural clay ground soil (CGS) was selected for this study since it corresponds to a typical worst case scenario of a low plasticity stiff soil that is difficult to be eroded during jet-grouting [6,7]. Natural clay ground soil was dried at 105°C for 5 days in an electrical laboratory oven and then sieved in order to pass a 2 mm sieve.…”
Section: Materials and Analytical Techniquesmentioning
confidence: 99%
See 3 more Smart Citations